Gender differences in the associations between knee pain and urinary incontinence in older adults: Cross-sectional analysis from the Malaysian Elders Longitudinal Research Study (MELoR) - Sumaiyah, Mat; Mohamad Hasif, Jaafar; Azad, Hassan Razack; Lim, Jasmine; Ong, Teng Aik; Khong, Su Yen; Shahrul, Bahyah Kamaruzzaman; Chin, Ai-Vyrn; Azlina, Amir Abbas; Chan, Chee Ken; Noran, Naqiah Hairi; Sajaratulnisah, Othman; et al. (Wiley, 2023)
Introduction: The common assumption that urinary incontinence occurs in osteoarthritis (OA) due to poor mobility is supported by limited evidence. The influence of gender in such associations is also yet to be elucidated.